The Complexity of Assessing Student Work Using Comparative Judgment: The Moderating Role of Decision Accuracy - van Daal, Tine; Lesterhuis, Marije; Coertjens, Liesje; van de Kamp, Marie-Thérèse; Donche, Vincent; De Maeyer, Sven (Frontiers in Education, 2017)
Nowadays, comparative judgment is used to assess competences. Judges compare two pieces of student work and judge which of both is better regarding the competence assessed. Using these pairwise comparison data, students’ work is scaled according to its quality. Since student work is highly information loaded and heterogeneous of nature, this raises the question whether judges can handle this type of complex judgments? However, research into the complexity of comparative judgment and its relation with decision accuracy is currently lacking. Therefore, this study initiates a theoretical framework on the complexity of comparative judgment and relates it to decision accuracy. Based on this framework two hypotheses are formulated and their plausibility is examined. The first hypothesis states that the distance between two pieces of student work on the rank-order (rank-order distance) is negatively related to experienced complexity, irrespectively of decision accuracy. In contrast, hypothesis 2 expects decision accuracy to moderate the relation between rank-order distance and experienced complexity. A negative relation is expected for accurate decisions. Meanwhile, inaccurate decisions are assumed to result in higher experienced complexity than accurate decisions, irrespective of rank-order distance. In both hypotheses, judges are expected to vary in mean experienced complexity as well as in the strength of the expected relationship between rank-order distance and experienced complexity. Using an information-theoretic approach, both hypotheses are translated into a statistical model and their relative fit is assessed. All analyses are replicated on three samples. Sample 1 and 2 comprise CJ data on the assessment of writing, while sample 3 contain pairwise comparison data on the assessment of visual arts. Results unambiguously confirm the moderating role of decision accuracy (hypothesis 2). Inaccurate decisions are experienced as more complex than accurate decisions, irrespective of rank-order distance. Meanwhile, for accurate decisions, rank-order distance is negatively related to experienced complexity. In line with expectations, differences between judges are found in mean experienced complexity and in the strength of the relationship between rank-order distance and experienced complexity. Suggestions for further theory development are formulated based on the results of this study.